2008
DOI: 10.1007/s11121-008-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Risks among Men and Women Who Drink at Informal Alcohol Serving Establishments (Shebeens) in Cape Town, South Africa

Abstract: HIV/AIDS is devastating southern Africa and the spread of HIV is fueled in some populations by alcohol use. Alcohol serving establishments, such as informal drinking places or shebeens, often serve as high-risk venues for HIV transmission. The current study examined the HIV risks of men (N = 91) and women (N = 248) recruited from four shebeens in a racially integrating township in Cape Town South Africa. Participants completed confidential measures of demographic characteristics, HIV risk history, alcohol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 24 publications
6
99
0
Order By: Relevance
“…A South African study by Townsend et al (2010) attempted to answer the question: ''Are condoms applied less effectively and consistently by men who drink heavily compared to those who do not?'' The study replicated findings from other studies, (Kalichman et al, 2008;Simbayi et al 2006) that heavy drinkers, if they use condoms, use them inconsistently.…”
Section: Condom Usesupporting
confidence: 83%
“…A South African study by Townsend et al (2010) attempted to answer the question: ''Are condoms applied less effectively and consistently by men who drink heavily compared to those who do not?'' The study replicated findings from other studies, (Kalichman et al, 2008;Simbayi et al 2006) that heavy drinkers, if they use condoms, use them inconsistently.…”
Section: Condom Usesupporting
confidence: 83%
“…A significant association between having met sex partners at a shebeen and unprotected vaginal sex versus those who did not meet partners at shebeens has been previously observed demonstrated [8]. Problem drinking was associated with having two or more sex partners in the last three months compared to those not having problem drinking [7].…”
Section: Discussionmentioning
confidence: 69%
“…In a study that compared patterns of problem alcohol use with regard to risk of testing HIV positive or having HIV risk factors, problem drinking was associated with having two or more sex partners in the last three months as compared to not having problem drinking (OR=3.0, 95% CI 1.9-4.4) [7]. Other research has suggested an association between having met sex partners at shebeens and unprotected vaginal sex (OR=1.1, 95% CI 1.1-1.2), as compared to those who did not meet partners at shebeens [8].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…shebeens). Kalichman and colleagues propose that it is not alcohol use that poses the risk, but the expectancies of high-risk individuals who frequent the alcohol outlets [6,7]. Similarly, the numerous studies observing associations between exposure to alcohol outlets and various types of violence typically propose a variety of mechanisms that avoid a central role for alcohol consumption [8][9][10][11][12].…”
mentioning
confidence: 99%